2012
DOI: 10.1681/asn.2011070668
|View full text |Cite
|
Sign up to set email alerts
|

Serum Amyloid A in Uremic HDL Promotes Inflammation

Abstract: Uremia impairs the atheroprotective properties of HDL, but the mechanisms underlying why this occurs are unknown. Here, we observed that HDL isolated from healthy individuals inhibited the production of inflammatory cytokines by peripheral monocytes stimulated with a Toll-like receptor 2 agonist. In contrast, HDL isolated from the majority of patients with ESRD did not show this anti-inflammatory property; many HDL samples even promoted the production of inflammatory cytokines. To investigate this difference, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
214
4
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(228 citation statements)
references
References 80 publications
6
214
4
4
Order By: Relevance
“…This effect was associated with a marked reduction in HDL anti-chemotactic activity. Other studies have confirmed that HDL lacks antiinflammatory properties in the majority of patients with ESRD, and in many cases can promote the production of inflammatory cytokines by macrophages in vitro 18 . The proinflammatory activity of HDL has been attributed to the presence of serum amyloid A in patients with ESRD.…”
Section: Srb1mentioning
confidence: 92%
See 1 more Smart Citation
“…This effect was associated with a marked reduction in HDL anti-chemotactic activity. Other studies have confirmed that HDL lacks antiinflammatory properties in the majority of patients with ESRD, and in many cases can promote the production of inflammatory cytokines by macrophages in vitro 18 . The proinflammatory activity of HDL has been attributed to the presence of serum amyloid A in patients with ESRD.…”
Section: Srb1mentioning
confidence: 92%
“…Normal HDL serves as a key driver against oxidative stress and the formation of proinflammatory oxidized lipids and lipoproteins via its constituent antioxidant enzymes, paraoxonase-1 and glutathione peroxidase, which can inhibit and/or reverse LDL oxidation. Moreover, HDL serves a protective role against systemic inflammation by removing oxidized phospholipids and fatty acids from LDL, VLDL, and IDL, removing endotoxin and serum amyloid-A from the circulation 17,18 , and promoting their disposal in the liver. Finally, normal HDL inhibits the attachment of monocytes to endothelial cells by inhibiting expression of vascular cell adhesion mol ecule-1 (VCAM-1) and intercellular adhesion molecule-1 (ICAM-1) on endothelial cells 19,20 and CD11b on monocytes 21 (FIG.…”
Section: Biologic Functions Of Normal Hdlmentioning
confidence: 99%
“…[3][4][5] Abnormalities of HDL structure and function in advanced CKD are mediated by a reduction in the serum levels of apoA-I and apoA-II (owing to reduced biosynthesis and increased catabolism), deficiency of lecithin cholesterol acyltransferase (LCAT, which is essential for esterification of free cholesterol on the surface of HDL and the formation of CE-rich HDL), upregulation of acyl c oenzyme A:cholesterol acyltransferase 1 and 2 (ACAT-1 and 2, which promote esterification and retention of intracellular cholesterol), oxidative modification of HDL 3,4 (which lowers its affinity for binding to ATPbinding cassette sub-family A member 1 [ABCA1] and ATP-binding cassette subfamily G member 1, the gateways of cholesterol efflux), 6 a reduction in the levels of the key HDL-associated antioxidant enzymes, serum paraoxonase/arylesterase 1 and glutathione peroxidase 1, 4,5 and the presence of highly proinflammatory serum amyloid A protein (SAA) in the HDL of patients on haemodialysis. 7 Hypoalbuminaemia (caused by systemic inflammation and malnutrition, which are fairly common in patients with ESRD) also contributes to reduced HDL-cholesterol levels by limiting receptorindependent transfer of albumin-bound chol esterol to HDL in the blood stream. These abnormalities work in concert to lower HDL levels and impair HDL maturation as well as its antioxidant, anti-inflammatory and reverse cholesterol transport capacities.…”
mentioning
confidence: 99%
“…In patients on haemodialysis, the ability of HDL to remove cholesterol from lipid-laden macro phages, 8 reverse LDL oxidation and prevent monocyte attachment to, and infiltration of, the vascular endothelium 7 is greatly reduced. HDL from patients with ESRD can trigger the release of inflammatory cytokines by macrophages, 7,8 a phenomenon that is partly attributable to the presence of SAA. 7 The mechanism that underlies the elevated serum HDL cholesterol levels in a subgroup of patients with ESRD in the study by Silbernagel et al, 1 and in other studies, 9,10 is unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation